2016
DOI: 10.2139/ssrn.2722535
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Policy and Corporate Bond Returns

Abstract: We investigate the impact of monetary policy shocks (the surprise change in the Fed Funds rate (FFR)) on excess corporate bonds returns. We obtain a significant negative response of bond returns to FFR shocks. This effect is especially strong in the period before the 2007-09 financial crisis and for bonds with longer maturity and lower rating. We show that the largest portion of this response is related to higher expected excess bond returns, especially term premia news. Therefore, the discount-rate channel re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…The effect is smaller compared to Figure 8 (between 50 and 25 bps, declining over time) but precisely estimated, an indication that roughly 40% of the stimulus effect that goes through corporate spreads comes from a pure reduction in risk premia and the remaining 60% from a decline in priced default probability risk. Similarly, a MEP shock reduces the premium by 30 bps in the initial months and the effect slowly converges to zero, being still 28 This is consistent with the empirical findings in Kontonikas et al (2020) for the GFC period and with the result in Figure 6 that the negative relationship between changes in short rates and spreads is most pronounced for lower-rated corporate credits, a segment of the market that was especially vulnerable to adverse macroeconomic shocks during the early stages of the GFC. 29 During a crisis, IGST bonds may become illiquid and this may increase their yields above the level justified by a decline of the riskless rate as well as of the default risk premia induced by QE.…”
Section: 5supporting
confidence: 84%
See 2 more Smart Citations
“…The effect is smaller compared to Figure 8 (between 50 and 25 bps, declining over time) but precisely estimated, an indication that roughly 40% of the stimulus effect that goes through corporate spreads comes from a pure reduction in risk premia and the remaining 60% from a decline in priced default probability risk. Similarly, a MEP shock reduces the premium by 30 bps in the initial months and the effect slowly converges to zero, being still 28 This is consistent with the empirical findings in Kontonikas et al (2020) for the GFC period and with the result in Figure 6 that the negative relationship between changes in short rates and spreads is most pronounced for lower-rated corporate credits, a segment of the market that was especially vulnerable to adverse macroeconomic shocks during the early stages of the GFC. 29 During a crisis, IGST bonds may become illiquid and this may increase their yields above the level justified by a decline of the riskless rate as well as of the default risk premia induced by QE.…”
Section: 5supporting
confidence: 84%
“…Coherently with the findings by Bernanke and Mihov (1998), our results are consistent with a response of corporate yields to an expansionary shock that reflects the economic regime prevailing at the time when the shock occurs. Kontonikas et al (2020) have reported that, during the 2007-2009 financial crisis, which is mostly captured by our regime 3, the elevated uncertainty led to an increase in riskier (i.e., non-investment grade) yields, while policy rates were being sharply cut, which is a result in line with the positive and significant IRF estimated for NIG bonds.…”
Section: Effects Of a Conventional Monetary Expansionsupporting
confidence: 74%
See 1 more Smart Citation
“…Three related papers are Gilchrist and Zakrajšek (2013), Guidolin et al (2017), and Kontonikas et al (2020). Gilchrist and Zakrajšek have estimated the effects of the Fed's QE and MEP programs on corporate credit risk by also employing a heteroskedasticity-based, event study approach.…”
Section: Introductionmentioning
confidence: 99%
“…Cieslak et al (2016) report that the stock returns in the US are cyclical and centered on the FOMC meetings. For bonds, Hördahl et al (2015) investigate the movements of the yield curve after the release of major U.S. macroeconomic announcements, and Kontonikas et al (2016) study the dynamics of the corporate bond returns after monetary policy shocks. For the FX market, the above mentioned papers by Mueller et al (2017) and Karnaukh (2016) are the major references.…”
Section: Introductionmentioning
confidence: 99%